Reliability of isokinetic dynamometer for isometric assessment of ankle plantar flexor strength - Santy, F.-M.; Pernoud, A.; Barrué-Belou, S.; Fourchet, F.; Bothorel, H.; Samozino, P. (Physical Therapy in Sport, 2025)
Objective To evaluate isokinetic dynamometer reliability for isometric assessment of plantar flexor (PF) strength.